Synthesis of Novel Chiral Ammonium-Based Ionic Liquids Derived from Isosorbide and their Applications in an Asymmetric Aza Diels-Alder Reaction - Nguyen Van Buu, Olivier; Vo-Thanh, Giang (Letters in Organic Chemistry, 2007)
A novel family of chiral ammonium-based ionic liquids containing a chiral moiety and a free hydroxyl function has been designed and synthesized from isosorbide. The synthesis of these ionic liquids is easy and practical owing to the commercially available starting materials. These new chiral ionic liquids can be used as chiral reaction media as well as catalysts in asymmetric synthesis, which are currently being investigated in our laboratory.
Keywords: Danishefsky' s diene